From Hierarchy To Reciprocity: Re-Envisioning Teacher-Student Relations In Islamic Education Through Qira’ah Mubadalah - Mahmud Yunus Mustofa; Muh Syauqi Malik; Mikke Novia Indriani; Makmur Sofyan Mustofa (Sekolah Tinggi Islam Kendal, 2026)
Teacher-student relationships within the Islamic educational tradition are frequently characterized by a unidirectional, vertical hierarchy in which the student is relegated to a passive recipient of knowledge. This power imbalance often triggers pedagogical stagnation and, in extreme cases, manifests as physical violence or emotional detachment. This study proposes a paradigm shift by re-envisioning the dynamics of teacher-student relations through the lens of Mubādalah (Reciprocity). Employing a qualitative approach grounded in hermeneutic analysis, this paper deconstructs the conventional